THE EFFECT OF PHERETIMA ASPERGILLUM EXTRACT ON THE INCREASE OF HAIR FOLLICLES NUMBER IN DIABETIC ULCER GRADE II IN WISTAR RAT - Kristianto, Heri; Sari, Dwi Astika (ETN Centre Indonesia, 2016)
Background: Diabetic ulcer is the result of serious microvascular complication of diabetes mellitus that is caused by vascular insufficiency, resulting in dry skin, loss of taste, and a decrease in the number of hair follicles. Earthworm (Pheretima aspergillum) has a bioactive component of IGF-1 (insulin like growth factor 1), which can stimulate cell growth and survival. IGF-1 is involved in hair follicle growth by regulating cell proliferation and migration through the cellular mechanism of its receptor (IGF - 1R). This study aimed to determine the effect of earthworm extract on the increase of hair follicles number in rats induced diabetic ulcer stage II. Methods: This study used a true experimental posttest only controlled group design. Samples were randomly selected, divided into five groups: Normal Saline as a negative control group, Hydrogel as a positive control group, and the three treatment groups received earthworm extract via topical, oral, and topical-oral. Ulcer treatment is done for 21 days, on day 22, rats were euthanized. The numbers of hair follicles in skin tissue connecting to nervous fibers were identified using silver impregnation stain. Results: The results showed that the treatment groups that received earthworm extract had significantly higher number of hair follicles as compared to the control groups (p=0.000). The administration of earthworm extract via topical has an optimal effect on the increase of hair follicles numbers. Conclusion: It can be concluded that the extract of earthworm (Pheretima aspergillum) can increase the growth of hair follicles in rats diabetic models. Keywords: diabetic ulcer, earthworm (Pheretima aspergillum), hair follicles.